Springtime arctic ozone depletion forces northern hemisphere climate anomalies - Friedel, Marina; id_orcid:0 000-0001-7739-4691; Chiodo, Gabriel; id_orcid:0 000-0002-8079-6314; Stenke, Andrea; id_orcid:0 000-0002-5916-4013; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X; Fueglistaler, Stephan; Anet, Julien; id_orcid:0 000-0002-2949-1363; Peter, Thomas; et al. (Nature Geoscience, 2022)
ISSN:1752-0908 ISSN:1752-0894